Effects of Carbon Nanohorn Based Nanofluids Pool Boiling on Optical Properties and Wettability of Different Metal Surfaces. Issue 19 (13th November 2021) - Gimeno-Furio, Alexandra; Hernandez, Leonor; Barison, Simona; Agresti, Filippo; Bottaro, Gregorio; Cabaleiro, David; Doretti, Luca; Mancin, Simone
Abstract: Oxidized carbon nanohorn water based nanofluids are attracting more and more attention for solar harvesting applications because of their peculiar features: stable suspension without any surfactant, higher solar absorbance values as compared to the base fluid, etc. However, these nanofluids are still matter of research because not all their properties have been comprehensively studied yet. This paper is focused on the wettability properties of the carbon nanohorn water based nanofluids on different metal surfaces. The static contact angle was measured for ten nanofluids with concentrations ranging from 0.002%wt to 0.1% wt, five of those used non-oxidized carbon nanohorns while the other five used oxidized carbon nanohorns. Moreover, this work investigates a novel use of the oxidized carbon nanohorn nanofluids to deposit an ultra-thin layer via pool boiling. The realized coating was proved to be stable and found to slightly affect the wettability of the nanofluids. Finally, the solar reflectance of the coated aluminum sample was measured and found to be from 2 to 10 times lower as compared to a reference aluminum surface.